Recombinant Erythropoietin Extraction By Immunoaffinity Column And The Detection Of Isoforms Using Capillary Electrophoresis - Al-Jaber, Hend Sultan A.S. (2013)
Erythropoietin (EPO) is an endogenous glycoprotein hormone. It is synthesized in and secreted mostly by the kidneys. In the market, there are a number of pharmaceuticals of recombinant EPO (rEPO) for clinical use. With the advent of novel technologies in the pharmaceutical and therapeutic areas, recombinant EPO have been introduced into the market. Although recombinant EPO has been broadly used to treat various forms of anaemia, it has also become a very well known drug due to its misuse in endurance sports. Sport authorities have prohibited the use of rEPO since 1989. This work has used a number of techniques to purify natural EPO and the recombinant form from the urine. Two Immunoaffinity column techniques (IAC) were used to purify EPO i.e. HiTrap Affinity Columns and MAIIA EPO Purification Kit. Both columns were successfully able to trap EPO molecules. EPO recovery from the HiTrap columns was negligible < 1%, whereas the recovery of MAIIA affinity column was satisfactory. The work has also developed a novel characterization tool using Capillary Electrophoresis (CE) that can be used in pharmaceutical Quality Control (QC) and has been investigated for its ability to detect drug misuse in sport. Conventional CE tools generally use a label that attaches to the EPO for identification.